Concessionaires, financiers and communities : implementing indigenous peoples' rights to land in transnational development projects / Kinnari I. Bhatt. - Bhatt, Kinnari I, 1978- (Cambridge University Press, 2020)
Unrelenting demands for energy, infrastructure and natural resources, and the need for developing states to augment income and signal an 'enterprise-ready' attitude mean that transnational development projects remain a common tool for economic development. Yet little is known about the fragmented legal framework of private financial mechanisms, contractual clauses and discretionary behaviours that shape modern development projects. How do gaps and biases in formal laws cope with the might of concessionaires and financiers and their algorithmic contractual and policy technicalities negotiated in private offices? What impacts do private legal devices have for the visibility and implementation of Indigenous peoples' rights to land? This original perspective on transnational development projects explains how the patterns of poor rights recognition and implementation, power(lessness), vulnerability and, ultimately, conflict routinely seen in development projects will only be fully appreciated by acknowledging and remedying the pivotal role and priority enjoyed by private mechanisms, documentation and expertise.